STRATEGIES TO ENSURE ORGANISATIONAL LEARNING TO GAIN COMPETITIVE ADVANTAGE IN GE - Farrag, Sadek (2010)
A considerable amount of thoughtful literature suggests that organisations with learning capabilities can gain competitive advantage over rivals. Much of this literature is divided into providing description of learning process led by Argyris and his notion of learning loops, the other proposes a set of management practices to build learning organisations led by Senge. This dissertation’s main contribution is to provide structured information about the recommended approach as well as best practices to build a learning organisation. It will examines the extent to which organisational learning concepts and disciplines, developed by Argyris and Senge, could be implemented and practiced in the day to day business and which are elusive. A case study is performed as a way to examine this in GE Company. A limitation of the study is the small number of interviews conducted to develop the case study; hence, generalisation would not be feasible. Moreover, the project has not measured the performance of the company under study to validate the competitive advantage, but the case study was carried out on a company that is well-known by its learning capabilities and recognised as a learning organisation.